Comparison of direct examination and in vitro culture for the detection of blastocystis sp. in Orang Asli stool samples - Samseh Abdullah Noradilah,; Norhayati Moktar,; Lee, Ii Li; Fatmah Md Salleh,; Tengku Shahrul Anuar, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Microscopy-based technique has been widely used in the detection of Blastocystis sp. This study was conducted to compare the techniques used for screening of Blastocystis sp., namely in vitro cultivation of stool specimens in Jones’ medium (IVC) followed by Wheatley Trichrome staining and direct examination of stool samples preserved with polyvinyl alcohol (PVA) followed by Wheatley Trichrome staining with single-round polymerase chain reaction (PCR) as the reference technique. The study was performed on 466 stool samples obtained from the aboriginal community in Pahang, Malaysia. IVC showed higher detection rate of Blastocystis sp. (35.6%) than PVA (20.0%). Single-round PCR detected Blastocystis sp. in 41.0% of the stool specimens. The sensitivity and specificity of PVA and IVC in comparison to the reference technique were 75.3% (95% CI: 65.2-83.6) and 68.5% (CI: 63.7-73.3) and 88.6% (CI: 82.7-93.0) and 86.3% (CI: 81.9-90.0), respectively. The agreement between the reference technique and PVA showed statistically significant fair agreement by Cohen Kappa statistics of (K=0.318, p<0.001), meanwhile statistically significant substantial agreement was observed between PCR and IVC by Cohen Kappa (K=0.727, p<0.001). Therefore, in vitro cultivation in Jones’ medium followed by Wheatley Trichrome staining of stool specimens should be used as a screening technique in the detection of Blastocystis sp. infections.